Modelado de la gestión entre parqueaderos y vehículos mediante la implementación de agentes inteligentes (2020)
Faced with the growing and accelerated settlement of the world population within large main cities, it makes this population density a challenge around the evolution of the city itself towards a more efficient (or intelligent) one, within this context there is a sub field dedicated to mobility and all the challenges it currently faces, being the planning and proper use of parking spaces somewhat preponderant, since it has been shown that this impacts vehicle flow significantly depending on the time of day or the season of the year. This work proposes a prototype model that allows management between parking lots and vehicles through the implementation of intelligent agents. Following an adequate methodology, the model is integrated through a technology-based solution that implements artificial intelligence to help in planning the trips of the driver to the parking lot within the city.